2017
DOI: 10.3171/2017.6.peds17158
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging–guided laser interstitial thermal therapy as treatment for intractable insular epilepsy in children

Abstract: OBJECTIVESeizure onset within the insula is increasingly recognized as a cause of intractable epilepsy. Surgery within the insula is difficult, with considerable risks, given the rich vascular supply and location near critical cortex. MRI-guided laser interstitial thermal therapy (LiTT) provides an attractive treatment option for insular epilepsy, allowing direct ablation of abnormal tissue while sparing nearby normal cortex. Herein, the authors describe their experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 16 publications
0
50
2
Order By: Relevance
“…Other techniques based on thermoablation or laser ablation in adults are limited to single cases with poor outcome, without benefit regarding seizures and creating expressive aphasia due to injury of the arcuate fasciculus or seizure‐free outcome but cognitive decline . However, one pediatric series has recently reported a favorable outcome in 10 of 20 patients using laser interstitial thermal therapy, showing that this technique may be an option for insular epilepsy in selected patients. Thermoablations combined with cortectomies reportedly resulted in up to 80% of patients achieving seizure freedom, with 20% experiencing postoperative complications (including 5% of permanent morbidity); however, the additional value of combining both procedures was undetermined .…”
Section: Discussionmentioning
confidence: 99%
“…Other techniques based on thermoablation or laser ablation in adults are limited to single cases with poor outcome, without benefit regarding seizures and creating expressive aphasia due to injury of the arcuate fasciculus or seizure‐free outcome but cognitive decline . However, one pediatric series has recently reported a favorable outcome in 10 of 20 patients using laser interstitial thermal therapy, showing that this technique may be an option for insular epilepsy in selected patients. Thermoablations combined with cortectomies reportedly resulted in up to 80% of patients achieving seizure freedom, with 20% experiencing postoperative complications (including 5% of permanent morbidity); however, the additional value of combining both procedures was undetermined .…”
Section: Discussionmentioning
confidence: 99%
“…We report a mean hospital stay of 1.3 days, while Curry et al [4] reported 3.8 days, Lewis et al [3] reported 1.56 days, and Perry et al [11] reported 1.8 days. No postoperative fevers were noted.…”
Section: Discussionmentioning
confidence: 58%
“…In 2017, Lewis et al [3] showed a 47% Engel I or II outcome over a mean follow-up duration of 16.1 months in a mixed cohort of 17 patients. In another study of 20 patients with insular epilepsy, Perry et al [11] showed 55% Engel I or II outcomes over a mean follow-up duration of 20.4 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LITT permits ablation of abnormal tissue while sparing normal cortex. Perry et al [34] reported results of 20 patients which had in 70% normal MRIs. After LITT 50% postoperative were in Engel class 1 and 5% in class 2.…”
Section: Treatmentmentioning
confidence: 99%